Visually Tracking and Localizing Expanding and Contracting Objects. (December 2013) - Howe, Piers D L; Holcombe, Alex O; Lapierre, Mark D; Cropper, Simon J
The maintenance of attention on moving objects is required for cognition to reliably engage with the visual world. Theories of object tracking need to explain on which patterns of visual stimulation one can easily maintain attention and on which patterns one cannot. A previous study has shown that it is easier to track rigid objects than objects that expand and contract along their direction of motion, in a manner that resembles a substance pouring from one location to another (vanMarle and Scholl 2003 Psychological Science 14 498–504). Here we investigate six possible explanations for this finding and find evidence supporting two of them. Our results show that, first, objects that expand and contract tend to overlap and crowd each other more, and this increases tracking difficulty. Second, expansion and contraction make it harder to localize objects, even when there is only a single target to attend to, and this may also increase tracking difficulty. Currently, there is no theory of object tracking that can account for the second finding.